An estimate on in‐construction differential settlement of super high‐rise frame core–tube buildings. (7th March 2020) - He, Zheng; Lu, Yi; Liu, Fengning; Pan, Feng; He, Shuaishuai
SUMMARY: To physically identify the mechanisms behind the development of in‐construction settlement of super high‐rise frame core–tube buildings, a simplified approach is developed by the full understanding about the typical structural layouts, specific construction feature, and load transfer path of those buildings as well as time‐dependent effects. With the reference to several typical structural layouts, a simplified one‐bay multistory model is developed that consists of two overall vertical components and horizontal components representing the exterior columns, core tubes, and beams (or mega trusses), respectively, in those super high‐rise buildings. Based on this model, a simplified approach with a so‐called "global–local" strategy is proposed to account for the difference in the settlement of the corner columns and side columns. The leading construction and final screwing at the rigid connections between beams (or trusses) and exterior columns, which are commonly implemented during the construction of those buildings, are seriously addressed in the simplified approach, as well as strengthened floors and time‐dependent effects. The applicability and accuracy of the proposed approach is demonstrated by a 128‐story 606‐m‐level super high‐rise frame core–tube building. The proposed simplified approach can be helpful for the development of preliminary construction schemes and the control strategy for differential settlement.